Letter from James Curtis Booth to A. L. Snowden, May 8, 1879 - Booth, James Curtis (1879)
James Curtis Booth (1810-1888) writes to Archibald Loudon Snowden (1835-1912), Superintendent of the United States Mint at Philadelphia from 1879 to 1885, in a long letter in which Booth expresses his views on allowing the Philadelphia Mint to be used for training purposes; he approves.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; Employees--Training of; Snowden, Archibald Loudon, 1835-1912